1995
DOI: 10.1055/s-2007-1005682
|View full text |Cite
|
Sign up to set email alerts
|

Hemangioma of the Esophagus: Endosonographic Imaging and Endoscopic Resection

Abstract: A 49-year-old Japanese man was seen to have an esophageal tumor on a routine barium swallow examination. Endoscopy revealed a sessile polyp covered by an almost normal esophageal mucosa, and the bioptic histology was non-diagnostic. Endoscopic ultrasonography showed a hypoechoic tumor with a diameter of 12 mm, confined to the submucosal layer, with the underlying muscularis propria layer being intact. On the basis of this finding, endoscopic resection was chosen and the tumor was resected using a two-channel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
1
14
0
3
Order By: Relevance
“…Carcinoid tumors larger than 2 cm in maximal cross-sectional dimension on EUS are more likely to be malignant. 18 Pancreatic rests may appear as hypoechoic or mixed echogenicity lesions in the second, third, or fourth layer. 6 Cysts appear as anechoic, rounded or ovoid, compressible structures in the third layer of the GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoid tumors larger than 2 cm in maximal cross-sectional dimension on EUS are more likely to be malignant. 18 Pancreatic rests may appear as hypoechoic or mixed echogenicity lesions in the second, third, or fourth layer. 6 Cysts appear as anechoic, rounded or ovoid, compressible structures in the third layer of the GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition, the role of endoscopic ultrasound (EUS) in accurately staging duodenal NETs is unclear. 6,7 EUS has frequently been used as an adjunct to EMR to determine depth of invasion for NETs in other parts of the GI tract. In a recent report by Holinga et al, 8 patients who underwent EMR of rectal NETsr10 mm in size were found to have local lymph node metastasis in 9% of cases in the absence of any high-risk histologic features, suggesting that EUS examination pre-EMR may be a critical part of initial evaluation of rectal NETs.…”
mentioning
confidence: 99%
“…Endoscopic ultrasound (EUS) showed a hypoechoic mass localized to the submucosa (• " Fig. 2) [5] and computed tomography (CT) revealed a hyperdense mass that was not invading the surrounding organs. The mass was diagnosed as a submucosal hemangioma of the esophagus.…”
mentioning
confidence: 99%